Influence of different kaolin concentrations (Surround WP®) on the attractiveness and mortality of Spodoptera frugiperda in corn (Research, Society and Development, 2025)
This study aimed to evaluate the effect of different  Surround WP® (an aluminum silicate-based product) concentration on the attractiveness and mortality of the fall armyworm (Spodoptera frugiperda) in corn plants (Zea mays L.). The experiment was conducted under greenhouse and laboratory conditions using five treatments: a control (no product) and four concentrations of Surround WP® (12.5 g, 25.0 g, 50.0 g, and 100 g/L of water). Treated leaves were used in feeding deterrence tests at 24, 48, and 72 hours, and in a mortality test conducted over 12 consecutive days. The results indicated that the concentration of 50 g/L was the most attractive to 1st instar caterpillars and caused the greatest mortality of S. fugiperda. Higher doses did not result in greater effects, suggesting optimal action at intermediate concentrations. The data obtained reinforces the potential of aluminum silicate as a viable alternative for integrated pest management.